2009
DOI: 10.1111/j.1365-313x.2009.03825.x
|View full text |Cite
|
Sign up to set email alerts
|

DWARF AND LOW‐TILLERING, a new member of the GRAS family, plays positive roles in brassinosteroid signaling in rice

Abstract: SUMMARYRapid progress has been made regarding the understanding of brassinosteroid (BR) signaling in Arabidopsis. However, little is known about BR signaling in monotyledons. Here, we characterized a rice dwarf and lowtillering (dlt) mutant and cloned the corresponding gene via map-based cloning. DLT encodes a new member of the plant-specific GRAS family. The dwarf phenotype of dlt is similar to BR-deficient or signaling mutants in rice. In addition, both lamina bending and coleoptile elongation assays show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
296
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 338 publications
(334 citation statements)
references
References 42 publications
9
296
0
6
Order By: Relevance
“…Genes GRAS19 (Chen et al, 2013), LAZY1 (Li et al, 2007), CYP51G3 (Xia et al, 2015), and GSR1 ) present high expression levels at the lamina joint, validating their roles in lamina joint development. In addition, genes involved in the biosynthesis and signaling of BR and auxin, which have been implicated in important roles in the leaf angle, present diverse expression patterns, including decreased expression (CYP51G3 and CYCU4:1), increased expression (DLT [Tong et al, 2009] and GRAS19 and GH3-2 [Tong et al, 2012]), constant high expression levels (LIC and LAZY1 [Zhang et al, 2012]), and constant low expression levels (ILI1 [Zhang et al, 2009a] and REL1 [Chen et al, 2015a]), suggesting the complex regulation of leaf angles via different pathways.…”
Section: Cytological Observation Reveals the Distinct Characteristicsmentioning
confidence: 99%
“…Genes GRAS19 (Chen et al, 2013), LAZY1 (Li et al, 2007), CYP51G3 (Xia et al, 2015), and GSR1 ) present high expression levels at the lamina joint, validating their roles in lamina joint development. In addition, genes involved in the biosynthesis and signaling of BR and auxin, which have been implicated in important roles in the leaf angle, present diverse expression patterns, including decreased expression (CYP51G3 and CYCU4:1), increased expression (DLT [Tong et al, 2009] and GRAS19 and GH3-2 [Tong et al, 2012]), constant high expression levels (LIC and LAZY1 [Zhang et al, 2012]), and constant low expression levels (ILI1 [Zhang et al, 2009a] and REL1 [Chen et al, 2015a]), suggesting the complex regulation of leaf angles via different pathways.…”
Section: Cytological Observation Reveals the Distinct Characteristicsmentioning
confidence: 99%
“…There is evidence that the rice heterotrimetric G protein a1 plays a role in BR signaling (Wang et al, 2006a;Oki et al, 2008). A few BR-regulated rice genes have been shown to contribute to BR-regulated development, including a direct target gene of BZR1 (Tong et al, 2009;Wang et al, 2009). Furthermore, many studies have shown important roles of BR in specific developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted using the TRIzol kit according to the user manual (GenStar; Tong et al, 2009). Two micrograms of total RNA treated with DNase I was used for cDNA synthesis with an RT kit (Promega).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%